Ensaio teórico: estudo comparativo das abordagens de execução estratégica - Serafini, Daiana dos Santos (Universidade do Vale do Rio dos Sinos, 2015)
The new economic environment which the companies operate intensely needs to run effective strategic in order to facilitate the search of the planned results. In this context, this activity must represent one of the main purposes of the managers and executives, since the understanding and proper studying the subject could help the strategic management in the business environment. Due to this background, the purpose of this article focuses on analysing the comparative approches on Strategic Execution viewing certain works selected and consulted. To this end, they researched up specific indications, verifying the synthesis and treatment of the theme in each, to later analyze the professional profile of those responsible and to assess their influence in several publications, comparing some of the factors that describe Execution strategic. Finally, there was the degree of emphasis to the subject in relation to the challenges presented to conclude that it comes to texts with great understanding and presentation, which shows the complexity of an issue that is becoming increasingly More important for business management.
Keywords: Administração estratégica; Gestão estratégica; Execução estratégica; Strategic management; Strategic execution